A Randomized Controlled Trial of a Play-Based, Peer-Mediated Pragmatic Language Intervention for Children With Autism - Parsons, Lauren; Cordier, Reinie; Munro, Natalie; Joosten, Annette (Frontiers in Psychology, 2019)
Purpose: This randomised controlled trial evaluated the effectiveness of a play-based pragmatic language intervention for children with autism. Methods: A sample of 71 children with autism were randomised to an intervention-first group (n =28 analysed) or waitlist-first (n = 34 analysed) group. Children attended ten, weekly clinic play-sessions with a typically-developing peer, and parents mediated practice components at home. The Pragmatics Observational Measure (POM-2) and the Social Emotional Evaluation (SEE) evaluated pragmatics before, after and 3-months following the intervention. Results: POM-2 gains were greatest for intervention-first participants (p=0.031, d=0.57). Treatment effects were maintained at 3-month follow-up (p<0.001-0.05, d=0.49-0.64). POM-2 scores were not significantly different in the clinic and home settings at follow-up. Conclusions: Findings support the combination of play, peer-mediation, video-feedback and parent training to enhance pragmatic language in children with autism.